PELATIHAN PENGGUNAAN MEDIA PEMBELAJARAN ICT GAME INTERAKTIF BAGI GURU-GURU SEKOLAH DASAR DI KECAMATAN BULELENG - Ni Made Ratmingsih; I Gede Budasi; I Gede Batan (Forum Layanan IPTEKS Bagi Masyarakat (FLipMAS) Wilayah Bali, 2019)
In this globalized era English plays a central role for international competition. This fact leads the government to give the opportunity to introduce English in the primary schools as the local content subject. One of the important components to make learning successful is instructional media, which is used by the teacher during teaching and learning process. The purpose of this social service program is to assist elementary school teachers in Buleleng district to improve their knowledge and skill in using ICT based interactive game and to improve the students’ motivation and learning achievement. The method of the program was technology transfer which was conducted through traning in using technology in this case ICT based interactive game, and in-service training in which the participants were given training and direct tutorial to the 4 representative schools representing 24 elementary schools of 17 sub-districts in Buleleng district. From those 17 sub-districts, there were 24 teachers, who taught English subject, were given training to use ICT based interactive game, which further was followed with designing a simple teaching scenario in the group. One representative of the 4 groups was then appointed to practice teaching simulation in the form of peer teaching. The program was continued with direct tutorial to the 4 representative schools involving 4 teachers representing eastern, western, southern, and northern parts of Buleleng district. The results of the program proves that (1) the training of using ICT based interactive game was valued very effective in improving the teachers’ knowledge and skills with the total score of effectiveness 91.67 categorized as very good, (2) there was improvement in the teachers skills in designing the lesson plan and conducting instruction shown from the result of direct tutorial and classroom observation using N1 and N2 forms. In designing the lesson plan, the teachers’ skill was 90% in the first tutorial which became 92% in the second tutorial categorized as very good, while in conducting instruction, the teacher’s skill also had similar result 90% in the first tutorial which became 92% in the second tutorial. Furthermore, the students’ achievement also shows improvement after being taught using ICT based interactive game, that is from 69.88 (categorized as moderate) which became 87.15 (very good). In terms of motivation, the score was 89, which means that the students had a very good motivation in studying English with the use of ICT based interactive game.